17 years of service-dominant logic: Vargo and Lusch’s contributions - Wibowo, Alexander Joseph Ibnu; Sumarwan, Ujang; Suharjo, Budi; Simanjuntak, Megawati (Business: Theory and Practice, 2021)
This article aims to examine the contribution of Vargo and Lusch (V&L) to service-dominant logic (S-D logic) thinking from the first time it appeared until now. No previous study has specifically analyzed all contributions of V&L since the phenomenon appearance of their article about this perspective in 2004. We identified a total of 146 titles of scientific publications by V&L with other authors on the S-D logic perspective over a period of 17 years (2004–2020). Each publication was analyzed through content analysis in several key aspects. This study found that the types of publications were dominated by journal articles and book chapters. There are 95 names of authors who have collaborated with V&L, mostly from the Americas and Europe. Based on the organization of origin of the researcher, 64 organizations have collaborated with V&L. All V&L publications are spread across 44 scientific journals, which include marketing and non-marketing journals or those from other social sciences. As a novelty, this study succeeds in explaining the evolution of S-D logic research over time based on V&L works through a systematic investigation. In this study, V&L’s efforts to institutionalize S-D logic can be traced.